2013
DOI: 10.1155/2013/608393
|View full text |Cite
|
Sign up to set email alerts
|

A Wideband Waveguide Antenna with Nearly Equal E- and H-Plane Radiation Patterns

Abstract: A novel wideband waveguide antenna with excellent performance is proposed, which is composed of a coaxial-waveguide transition and an open-ended rectangular waveguide loaded with a pair of horizontal umbrella-shaped metallic brims. The brims perpendicular to two broad walls of the waveguide are constructed to modulate the antenna to radiate nearly identical E- and H-plane radiation patterns. A wideband impedance matching performance is achieved with a fractional bandwidth of 40% through the introduction of sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…3 . It can be observed that the distributions are rotationally symmetric, which is guaranteed by the feed with axially symmetric radiation patterns 36 . The symmetric property of the aperture field also guarantees the symmetric property of the beams generated by the lens.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…3 . It can be observed that the distributions are rotationally symmetric, which is guaranteed by the feed with axially symmetric radiation patterns 36 . The symmetric property of the aperture field also guarantees the symmetric property of the beams generated by the lens.…”
Section: Resultsmentioning
confidence: 93%
“…1(a) . This Bessel beam launcher includes two parts: one is the planar GRIN metamaterial lens and the other is a feed with axially symmetric radiation patterns 36 . In contrast to the axicon setup which needs Gaussian beams for excitation, the GRIN lens is illuminated by a nearly spherical wave emitted from the feed, a broadband waveguide antenna.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If a feeding source is placed in front of the metasurface with v polarization, then the incident waves are v -polarized waves, and the electric-field vector of E v can be decomposed to E x and E y with | E x | = | E y |, so the x - and y -polarized waves can be controlled independently by phase distributions of the metasurface in x and y directions, respectively. We remark that the feeding source used in our simulations and experiments is a linearly polarized Ku-band (12 GHz–18 GHz) coax-to-waveguide device with nearly equal E- and H-plane radiation patterns39. In the following, three specific examples are investigated by simulations to show the powerful ability of the proposed anisotropic metasurfaces in multi-beam reflections with independent control of polarizations.…”
Section: Resultsmentioning
confidence: 99%
“…The metasurfaces are composed of Jerusalem Cross structures and a grounded plane spaced by a dielectric substrate. A Ku-band coax-to-waveguide device is placed in front of the metasurfaces used as the feeding source, which can generate quasi-spherical incident waves with linear polarization39. The quasi-spherical incident waves can be reflected by the metasurfaces with high efficiency, while the reflected phases of x - and y -polarized waves can be controlled independently by changing the dimensions of the I-shaped structures on x and y directions, respectively.…”
mentioning
confidence: 99%